Tandem Ring‐Opening–Ring‐Closing Metathesis for Functional Metathesis Catalysts. Issue 40 (5th September 2016) - Nagarkar, Amit A.; Yasir, Mohammad; Crochet, Aurelien; Fromm, Katharina M.; Kilbinger, Andreas F. M.
Abstract: Use of a tandem ring‐opening–ring‐closing metathesis (RORCM) strategy for the synthesis of functional metathesis catalysts is reported. Ring opening of 7‐substituted norbornenes and subsequent ring‐closing metathesis forming a thermodynamically stable 6‐membered ring lead to a very efficient synthesis of new catalysts from commercially available Grubbs' catalysts. Hydroxy functionalized Grubbs' first‐ as well as third‐generation catalysts have been synthesized. Mechanistic studies have been performed to elucidate the order of attack of the olefinic bonds. This strategy was also used to synthesize the ruthenium methylidene complex. Abstract : The preferred reaction of a commercial ruthenium benzylidene complex with a highly strained norbornene, followed by a fast intramolecular cyclization, yields new ruthenium carbene complexes in excellent yields. These complexes are ready for functional initiation of polymerization reactions without the need of purification.